PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN MEDIA KONKRET UNTUK MENINGKATKAN PEMBELAJARAN MATEMATIKA TENTANG BANGUN RUANG PADA SISWA KELAS V SDN SURABAYAN TAHUN AJARAN 2016/2017 - Riana, Oka Yoga; Wahyudi, Wahyudi; Chamdani, Muhamad (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use Of Problem Based Learning (PBL) Model Using Concrete Media In Improving The Learning Of Mathematics About Geometry For The Fifth Grade Students Of SDN Surabayan In The Academic Year Of 2016/2017. The objective of this research is to improve the learning of mathematics about geometry through the use of problem based learning (PBL) model using concrete media. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles; two meetings each. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were 28 students. The results of this research show that the use of problem based learning (PBL) model using concrete media can improve the learning of mathematics about geometry for the fifth grade students of SDN Surabayan in the academic year of 2016/2017. Keywords: Problem Based Learning (PBL), Concrete Media, Mathematics Abstrak: Penerapan Model Problem Based Learning (PBL) dengan Media Konkret untuk Meningkatkan Pembelajaran Matematika tentang Bangun Ruang pada Siswa Kelas V SDN Surabayan Tahun Ajaran 2016/2017. Tujuan penelitian ini adalah meningkatkan pembelajaran matematika tentang bangun ruang melalui penerapan model Problem Based Learning (PBL) dengan media konkret. Penelitian ini merupakan penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas V SDN Surabayan yang berjumlah 28 siswa. Hasil penelitian ini menunjukkan bahwa penerapan model Problem Based Learning (PBL) dengan media konkret dapat meningkatkan pembelajaran matematika tentang bangun ruang pada siswa kelas V SDN Surabayan tahun ajaran 2016/2017. Kata kunci: Problem Based Learning (PBL), Media Konkret, Matematika